Fontes e modos de aplicação de boro na cultura do eucalipto (clone I144) - Celestrino, Thiago de Souza [UNESP] (2014)
Cerrado soils present low levels of boron being common supplementation of this element through soil and foliar fertilization. Therefore, it is important to define how better mode of application and source for the successful development and productivity of eucalyptus, with possible cost savings. Thus, this study aimed to compare the effect of B sources with high and low solubility applied in soil and high solubility applied on leaf of Eucalyptus spp. The experiment was conducted at farm Renascença, located in Três Lagoas/MS with latitude 20 34 'S and longitude 51 50' W and altitude of approximately 305 m, in 02/2012 to 02/2014. It was used a randomized block design with six treatments and five replications arranged in a factorial scheme 2 x 3, being: 0 kg ha- 1 B, 1 kg ha- 1 B, using boric acid as source (high solubility, 17 % B) or 1 kg ha-1 B, using as source borogran (low solubility, 10 % B), applied at planting, with or without application of boric acid foliar at 0.5% in a volume of 250 Lha-1. With the omission of B foliar there was an increase in plant height in treatments with the application of boron at planting, differing from the control. However, both of these sources, regardless of the solubility, showed similar results. The two foliar applications of B were sufficient for getting an increase in plant height when compared to treatments without B application at planting. At 18 and 24 months after planting there was increased on B foliar content in treatments with foliar application. Applying B at planting, regardless of source, as well as foliar application, were sufficient to reduce the symptoms of B deficiency. Regarding the sources used at planting, dose of 1kg ha-1 B, showed similar results on plant height, DBH and volume of wood. However, borogran increased the conten of B in the soil after 24 months of planting, from 20 to 40 cm layer, which can be beneficial for crop over time